Heresies and heretics memories of the twentieth century - Watson, George (Cambridge : Lutterworth Press, 2013)
In this enjoyably iconoclastic book, George Watson discusses some of the great heresies of the twentieth century, and the cultural heretics who espoused them, often with surprising results. Watson provides us with examples of 'true', original heretics, from Sir Arthur Quiller-Couch, who asserted that his study of the remote past had made a radical of him, rather than any influence of modernism, to others such as Douglas Adams, whom Watson knew as an undergraduate. Watson forces us to question various long-cherished political and intellectual assumptions in his witty and conversational style. Is.
""14. Educating the Prime Minister""""15. The Indictment of the Germans""; ""16. Thoughts on a Dead Elephant""; ""17. The Sudden Death of Imperial Guilt""; ""III The Heretics ""; ""18. P.G. Wodehouse""; ""19. The Forgotten Churchill""; ""20. Arthur Quiller-Couch""; ""21. E.M. Forster""; ""22. C.P. Snow""; ""23. Hugh Sykes Davies""; ""24. Angus Wilson""; ""25. Moses Finley""; ""26. Hugh Trevor-Roper""; ""27. Frank Kermode""; ""28. Douglas Adams""; ""You might also be interested in other titles by George Watson ""; ""Back cover ""
Master record variable field(s) change: 072
Keywords: Catholic Church -- Doctrines; Catholic Church; Catholic Church; Christian heresies; Christian heretics; RELIGION -- History; Christian heresies; Christian heretics; Theology, Doctrinal; PHILOSOPHY / General; Electronic books